A laminated composite film foot pad and preparation method thereof
Through the laminated composite coating process and modified burr cloth composite material, the problems of poor flame retardant effect and short-lasting antibacterial properties of automotive foot pads are solved, and high-strength, high flame retardant and excellent antibacterial properties are achieved.
Patent Information
- Application Number
- CN202410588889.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-05-13
AI Technical Summary
The existing automotive foot pad materials have poor flame retardant effects, are not long-lasting in antibacterial properties, and are prone to bacterial breeding and mold growth problems, which affects the service life.
The laminated composite film coating process is adopted, combining low-density polyethylene, polyethylene terephthalate and chemical crosslinked polyethylene foaming materials, and the composite treatment of thermoplastic elastomers and chemical crosslinked polyethylene foaming materials. Add modified burr cloth composite material, and use fluorine-containing silicone polyurethane and composite zinc phytate to prepare an antibacterial flame retardant impregnation liquid to improve the bonding strength and stain resistance of the material.
It has achieved high mechanical strength, excellent antibacterial properties and good antifouling properties, and has high flame retardant properties and good service life.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foot pads, in particular to a laminated composite film-coated foot pad and a preparation method thereof. Background Art
[0002] Car floor mats are car interior components. With the improvement of consumption level, car floor mats are also developing towards multi-functions. Currently, consumers not only pay attention to their basic functions of anti-slip and keeping clean, but also pay attention to their flame retardant, antibacterial, and easy to clean properties.
[0003] The materials of existing car floor mats on the market are mostly one of chemical fiber, polyvinyl chloride and rubber. Polyvinyl chloride and rubber floor mats have strong odor, poor flame retardant effect, and have certain safety hazards. In addition, the antibacterial property of current car floor mats is not long-lasting. The antibacterial property decreases after repeated washing. After long-term use, problems such as bacteria breeding and mold are prone to occur, which affects the service life of the floor mats. Summary of the invention
[0004] The object of the present invention is to provide a laminated composite coated foot pad and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a laminated composite film foot pad comprises the following steps:
[0007] S1: low-density polyethylene is put into the hopper of the compounding machine, and polyethylene terephthalate and chemically cross-linked polyethylene foam material are respectively fed into rollers from both ends of the compounding machine, compounded, and rolled to obtain a composite layer;
[0008] S2: Put the thermoplastic elastomer into the laminating machine hopper, clamp the chemically cross-linked polyethylene foam material between the rollers, perform coating treatment, and roll up to obtain a coating layer;
[0009] S3: Compounding the composite layer, the coating layer and the burr cloth composite material in sequence, heat setting and compression molding, to obtain a laminated composite coating foot pad.
[0010] Furthermore, the mass ratio of low-density polyethylene, polyethylene terephthalate, and chemically cross-linked polyethylene foam material in the composite layer is 2:1:1; the mass ratio of thermoplastic elastomer and chemically cross-linked polyethylene foam material in the coating layer is 1:3.
[0011] Furthermore, the working conditions of the composite treatment are: screw speed of 45rpm, die temperature of 280℃, die width of 1500mm, and discharge roller gap of 0.02-0.03mm; the working conditions of the coating treatment are: screw speed of 21.5Hz, roller speed of 6.65r / min; the working conditions of heat setting are: temperature of 120-160℃, time of 70-90s; the working conditions of compression molding are: time of 55-65s, pressure of 3-5MPa.
[0012] Furthermore, the preparation of the thermoplastic elastomer includes the following steps: SEBS, PP and PE are mixed in a weight ratio of 20:45:35 to obtain a mixture; the mixture, masterbatch, stabilizer, calcium powder and Optapol elastomer are mixed in a weight ratio of 87.6:0.3:0.1:2:10, extruded granulated, cooled, pelletized and dried to obtain the thermoplastic elastomer.
[0013] Furthermore, the preparation of the chemically cross-linked polyethylene foam material includes the following steps: mixing low-density polyethylene resin, a cross-linking agent, an azo foaming agent, and a masterbatch according to a weight ratio of 96:0.7:0.3:2, extruding, and foaming to obtain a chemically cross-linked polyethylene foam material.
[0014] Furthermore, the preparation of polyethylene terephthalate includes the following steps: mixing nylon particles and masterbatch in a weight ratio of 85:15, and melt spinning to obtain polyethylene terephthalate.
[0015] Furthermore, the burr cloth composite material is a modified burr cloth composite material, and the preparation thereof includes the following steps:
[0016] (1) Using fluorinated organosilicon polyurethane and composite zinc phytate to prepare an antibacterial flame retardant impregnation liquid;
[0017] (2) The burr cloth composite material is immersed in an antibacterial and flame retardant impregnation liquid, and then dried to obtain a modified burr cloth composite material.
[0018] Further, the preparation of composite zinc phytate comprises the following steps:
[0019] Mix zinc acetate and deionized water, heat to 78-82°C, add a mixture of phytic acid and deionized water, keep warm for 3-4 hours, wash and dry to obtain zinc phytate; mix zinc phytate and ethanol, add 3,4-dihydroxybenzaldehyde and quaternary ammonium glycogen, keep warm at 78-82°C for 2-3 hours, add DOPO, stir for 9-10 hours, filter, wash and dry to obtain composite zinc phytate.
[0020] Further, the preparation of fluorinated silicone polyurethane comprises the following steps:
[0021] 1) under a nitrogen atmosphere, isoborneol methacrylate, dodecafluoroheptyl methacrylate, 1-thioglycerol, azobisisobutyronitrile and tetrahydrofuran are mixed, the temperature is raised to 68-72° C. and kept for 9-10 hours, rotary evaporated, methanol is added, and dried to obtain a hydroxylated fluorinated borneol copolymer;
[0022] 2) In a nitrogen environment, tetrahydrofuran, hydroxyl-terminated polydimethylsiloxane and isophorone diisocyanate are mixed, the temperature is raised to 68-72°C and kept warm for 1-2 hours, hydroxylated fluorinated borneol copolymer is added and kept warm for 30-40 minutes, dibutyltin dilaurate and quaternary ammonium glycogen are added, the temperature is raised to 78-82°C and kept warm for 2-3 hours, triethanolamine is added and kept warm for 1-2 hours, and the material is discharged to obtain fluorinated silicone polyurethane.
[0023] Further, the preparation of quaternary ammonium salt glycogen comprises the following steps:
[0024] Under nitrogen protection, glycogen and anhydrous dimethyl sulfoxide are mixed, N,N-carbonyldiimidazole is added, and the mixture is stirred at 30-35°C for 1-2 hours. A mixture of ethylenediamine and dimethyl sulfoxide is added, and the mixture is kept warm at 18-25°C for 22-24 hours, dialyzed, and freeze-dried to obtain amino glycogen; the amino glycogen and deionized water are mixed, and the mixture is stirred at 58-62°C for 20-30 minutes. The pH is adjusted to 8-9, 2,3-epoxypropyltrimethylammonium chloride is added, and the mixture is kept warm for 5-6 hours. The mixture is dialyzed and freeze-dried to obtain quaternary ammonium glycogen.
[0025] Beneficial effects of the present invention:
[0026] The invention provides a laminated composite coated foot pad and a preparation method thereof, and a foot pad with good mechanical strength, excellent antibacterial property, good antifouling property and high flame retardancy is prepared by limiting raw materials and processes.
[0027] The present invention adopts a laminated composite coating process to improve the bonding strength between the materials and improve the mechanical properties of the foot pad. In order to give the foot pad excellent antibacterial and flame retardant properties, the burr cloth composite material is modified, and an antibacterial and flame retardant impregnation liquid is prepared using fluorine-containing silicone polyurethane and composite zinc phytate. The burr cloth composite material is immersed in the antibacterial and flame retardant impregnation liquid to give the burr cloth composite material excellent antibacterial, flame retardant and self-cleaning properties.
[0028] Organic silicon coating is an ideal environmentally friendly antifouling material, but its static antifouling ability is relatively poor. In the present invention, organic silicon prepolymer is synthesized with hydroxyl-terminated polydimethylsiloxane and isophorone diisocyanate as raw materials, and hydroxylated fluorinated borneol copolymer is synthesized by free radical polymerization of isoborneol methacrylate, dodecafluoroheptyl methacrylate and 1-thioglycerol, and quaternized glycogen is used as a chain extender, and triethanolamine is used as a capping agent to obtain fluorinated organic silicon polyurethane, and the fluorinated polymer is combined with the antifouling group to improve its static antifouling ability; wherein the quaternized glycogen is a stepwise chemical modification on the glycogen, and the amino group is first modified to the glycogen side chain, which is conducive to cross-linking with the fluorinated organic silicon polyurethane, enhancing the antibacterial and flame retardant durability, and because the reaction activity of the amino group is stronger than that of the hydroxyl group, it is conducive to subsequent quaternary ammonium salt modification, and the amino glycogen is quaternized to form a cationic dendritic macromolecular structure quaternized glycogen, and at the same time, it is endowed with excellent mechanical properties, good substrate adhesion, and excellent antibacterial properties.
[0029] Phytic acid is a biomass organophosphorus compound containing 6 phosphate groups and is an effective carbonizing agent, but its gas-phase flame retardant efficiency is low. In the present invention, phytic acid and zinc acetate are used to prepare zinc phytate, and then 3,4-dihydroxybenzaldehyde, quaternized glycogen and DOPO are used as raw materials to synthesize a Schiff base copolymer in one pot, and intermolecular forces are used to coat zinc phytate to prepare composite zinc phytate as a flame retardant and antibacterial agent, which is introduced into a flame retardant and antibacterial impregnation solution, and the synergistic effect of DOPO-based flame retardants is used to compensate for the low gas-phase flame retardant efficiency of phytic acid, to form a heat-insulating carbon layer during combustion, and to shield air, heat and pyrolysis products during thermal decomposition; wherein the introduction of quaternized glycogen gives the composite zinc phytate excellent antibacterial properties. DETAILED DESCRIPTION
[0030] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0032] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0033] Embodiment 1: A method for preparing a laminated composite film foot pad comprises the following steps:
[0034] S1: low-density polyethylene is put into the hopper of the compounding machine, and polyethylene terephthalate and chemically cross-linked polyethylene foam material are respectively fed into rollers from both ends of the compounding machine, compounded, and rolled to obtain a composite layer;
[0035] S2: Put the thermoplastic elastomer into the laminating machine hopper, clamp the chemically cross-linked polyethylene foam material between the rollers, perform coating treatment, and roll up to obtain a coating layer;
[0036] S3: Compounding the composite layer, the coating layer, and the burr cloth composite material in sequence, heat setting, and compression molding to obtain a laminated composite coating foot pad;
[0037] The mass ratio of low-density polyethylene, polyethylene terephthalate, and chemically cross-linked polyethylene foam material in the composite layer is 2:1:1; the mass ratio of thermoplastic elastomer and chemically cross-linked polyethylene foam material in the coating layer is 1:3;
[0038] The working conditions of composite treatment are: screw speed of 45rpm, die temperature of 280℃, die width of 1500mm, and discharge roller gap of 0.02mm; the working conditions of coating treatment are: screw speed of 21.5Hz, roller speed of 6.65r / min; the working conditions of heat setting are: temperature of 120℃, time of 90s; the working conditions of compression molding are: time of 55s, pressure of 5MPa;
[0039] The preparation of the thermoplastic elastomer comprises the following steps: mixing SEBS, PP and PE in a weight ratio of 20:45:35 to obtain a mixture; mixing the mixture, masterbatch, stabilizer, calcium powder and Optapol elastomer in a weight ratio of 87.6:
[0040] 0.3:0.1:2:10 mixing, extrusion granulation, cooling, pelletizing, drying, to obtain a thermoplastic elastomer;
[0041] The preparation of the chemically cross-linked polyethylene foam material comprises the following steps: mixing a low-density polyethylene resin, a cross-linking agent, an azo foaming agent, and a masterbatch according to a weight ratio of 96:0.7:0.3:2, extruding, and foaming to obtain a chemically cross-linked polyethylene foam material;
[0042] The preparation of polyethylene terephthalate comprises the following steps: mixing nylon particles and masterbatch in a weight ratio of 85:15, and melt spinning to obtain polyethylene terephthalate;
[0043] The burr cloth composite material is a modified burr cloth composite material, and the preparation thereof includes the following steps:
[0044] (1) The antibacterial flame retardant impregnation liquid was prepared by mixing fluorinated organosilicon polyurethane and composite zinc phytate in a mass ratio of 20:1;
[0045] The preparation of the composite zinc phytate comprises the following steps:
[0046] 5.5 g of zinc acetate and 50 mL of deionized water were mixed, the temperature was raised to 78°C, a mixture of 6.6 g of phytic acid and 25 mL of deionized water was added, the mixture was kept warm for 3 h, washed and dried to obtain zinc phytate; 2 g of zinc phytate and 100 mL of ethanol were mixed, 2 g of 3,4-dihydroxybenzaldehyde and 1.6 g of quaternary ammonium glycogen were added, the mixture was kept warm at 78°C for 3 h, 3.2 g of DOPO was added, the mixture was stirred for 9 h, filtered, washed and dried to obtain composite zinc phytate;
[0047] The preparation of the fluorinated organosilicon polyurethane comprises the following steps:
[0048] 1) Under a nitrogen atmosphere, 5.3 g of isoborneol methacrylate, 2.4 g of dodecafluoroheptyl methacrylate, 0.3 g of 1-thioglycerol, 0.02 g of azobisisobutyronitrile and 24 mL of tetrahydrofuran were mixed, the temperature was raised to 68° C. and kept for 10 h, rotary evaporated, 20 mL of methanol was added and dried to obtain a hydroxylated fluorinated borneol copolymer;
[0049] 2) In a nitrogen environment, 10 mL of tetrahydrofuran, 2 g of hydroxyl-terminated polydimethylsiloxane, and 0.7 g of isophorone diisocyanate were mixed, the temperature was raised to 68° C. and kept warm for 2 h, 0.4 g of hydroxylated fluorinated borneol copolymer was added and kept warm for 30 min, 1 drop of dibutyltin dilaurate and 0.14 g of quaternary ammonium glycogen were added, the temperature was raised to 78° C. and kept warm for 3 h, 0.03 g of triethanolamine was added and kept warm for 1 h, and the material was discharged to obtain fluorinated silicone polyurethane;
[0050] The preparation of the quaternary ammonium salt glycogen comprises the following steps:
[0051] Under nitrogen protection, 4 g of glycogen and 200 mL of anhydrous dimethyl sulfoxide were mixed, 4 g of N, N-carbonyldiimidazole was added, and the mixture was stirred at 30 ° C for 2 h, and a mixture of 6 mL of ethylenediamine and 10 mL of dimethyl sulfoxide was added, and the mixture was kept at 18 ° C for 24 h, dialyzed for 3 days, and lyophilized to obtain amino glycogen; 2 g of amino glycogen and 25 mL of deionized water were mixed, stirred at 58 ° C for 30 min, the pH was adjusted to 8, 1 g of 2, 3-epoxypropyltrimethylammonium chloride was added, and the mixture was kept warm for 5 h, dialyzed for 3 days, and lyophilized to obtain quaternary ammonium glycogen;
[0052] (2) The burr cloth composite material is immersed in an antibacterial and flame retardant impregnation liquid, and then dried to obtain a modified burr cloth composite material.
[0053] Embodiment 2: A method for preparing a laminated composite film foot pad comprises the following steps:
[0054] S1: low-density polyethylene is put into the hopper of the compounding machine, and polyethylene terephthalate and chemically cross-linked polyethylene foam material are respectively fed into rollers from both ends of the compounding machine, compounded, and rolled to obtain a composite layer;
[0055] S2: Put the thermoplastic elastomer into the laminating machine hopper, clamp the chemically cross-linked polyethylene foam material between the rollers, perform coating treatment, and roll up to obtain a coating layer;
[0056] S3: Compounding the composite layer, the coating layer, and the burr cloth composite material in sequence, heat setting, and compression molding to obtain a laminated composite coating foot pad;
[0057] The mass ratio of low-density polyethylene, polyethylene terephthalate, and chemically cross-linked polyethylene foam material in the composite layer is 2:1:1; the mass ratio of thermoplastic elastomer and chemically cross-linked polyethylene foam material in the coating layer is 1:3;
[0058] The working conditions of composite treatment are: screw speed of 45rpm, die temperature of 280℃, die width of 1500mm, and discharge roller gap of 0.025mm; the working conditions of coating treatment are: screw speed of 21.5Hz, roller speed of 6.65r / min; the working conditions of heat setting are: temperature of 140℃, time of 80s; the working conditions of compression molding are: time of 60s, pressure of 4MPa;
[0059] The preparation of the thermoplastic elastomer comprises the following steps: SEBS, PP and PE are mixed in a weight ratio of 20:45:35 to obtain a mixture; the mixture, a masterbatch, a stabilizer, calcium powder and an Optapol elastomer are mixed in a weight ratio of 87.6:0.3:0.1:2:10, extruded granulated, cooled, granulated and dried to obtain a thermoplastic elastomer;
[0060] The preparation of the chemically cross-linked polyethylene foam material comprises the following steps: mixing a low-density polyethylene resin, a cross-linking agent, an azo foaming agent, and a masterbatch according to a weight ratio of 96:0.7:0.3:2, extruding, and foaming to obtain a chemically cross-linked polyethylene foam material;
[0061] The preparation of polyethylene terephthalate comprises the following steps: mixing nylon particles and masterbatch in a weight ratio of 85:15, and melt spinning to obtain polyethylene terephthalate;
[0062] The burr cloth composite material is a modified burr cloth composite material, and the preparation thereof includes the following steps:
[0063] (2) preparing an antibacterial flame retardant impregnation liquid by mixing fluorinated organosilicon polyurethane and composite zinc phytate in a mass ratio of 20:1;
[0064] The preparation of the composite zinc phytate comprises the following steps:
[0065] 5.5 g of zinc acetate and 50 mL of deionized water were mixed, the temperature was raised to 80°C, a mixture of 6.6 g of phytic acid and 25 mL of deionized water was added, the mixture was kept warm for 3.5 h, washed and dried to obtain zinc phytate; 2 g of zinc phytate and 100 mL of ethanol were mixed, 2 g of 3,4-dihydroxybenzaldehyde and 1.6 g of quaternary ammonium glycogen were added, the mixture was kept warm at 80°C for 2.5 h, 3.2 g of DOPO was added, the mixture was stirred for 9.5 h, filtered, washed and dried to obtain composite zinc phytate;
[0066] The preparation of the fluorinated organosilicon polyurethane comprises the following steps:
[0067] 1) Under a nitrogen atmosphere, 5.3 g of isoborneol methacrylate, 2.4 g of dodecafluoroheptyl methacrylate, 0.3 g of 1-thioglycerol, 0.02 g of azobisisobutyronitrile and 24 mL of tetrahydrofuran were mixed, the temperature was raised to 70° C. and kept for 9.5 h, rotary evaporated, 20 mL of methanol was added and dried to obtain a hydroxylated fluorinated borneol copolymer;
[0068] 2) In a nitrogen environment, 10 mL of tetrahydrofuran, 2 g of hydroxyl-terminated polydimethylsiloxane, and 0.7 g of isophorone diisocyanate were mixed, the temperature was raised to 70° C. and kept warm for 1.5 h, 0.4 g of hydroxylated fluorinated borneol copolymer was added and kept warm for 35 min, 1 drop of dibutyltin dilaurate and 0.14 g of quaternary ammonium glycogen were added, the temperature was raised to 80° C. and kept warm for 2.5 h, 0.03 g of triethanolamine was added and kept warm for 1.5 h, and the material was discharged to obtain fluorinated silicone polyurethane;
[0069] The preparation of the quaternary ammonium salt glycogen comprises the following steps:
[0070] Under nitrogen protection, 4 g of glycogen and 200 mL of anhydrous dimethyl sulfoxide were mixed, 4 g of N, N-carbonyldiimidazole was added, and the mixture was stirred at 32 ° C for 1.5 h, and a mixture of 6 mL of ethylenediamine and 10 mL of dimethyl sulfoxide was added, and the mixture was kept at 20 ° C for 23 h, dialyzed for 3 days, and lyophilized to obtain amino glycogen; 2 g of amino glycogen and 25 mL of deionized water were mixed, stirred at 60 ° C for 25 min, the pH was adjusted to 8.5, 1 g of 2,3-epoxypropyltrimethylammonium chloride was added, and the mixture was kept warm for 5.5 h, dialyzed for 3 days, and lyophilized to obtain quaternary ammonium glycogen;
[0071] (2) The burr cloth composite material is immersed in an antibacterial and flame retardant impregnation liquid, and then dried to obtain a modified burr cloth composite material.
[0072] Embodiment 3: A method for preparing a laminated composite film foot pad comprises the following steps:
[0073] S1: low-density polyethylene is put into the hopper of the compounding machine, and polyethylene terephthalate and chemically cross-linked polyethylene foam material are respectively fed into rollers from both ends of the compounding machine, compounded, and rolled to obtain a composite layer;
[0074] S2: Put the thermoplastic elastomer into the laminating machine hopper, clamp the chemically cross-linked polyethylene foam material between the rollers, perform coating treatment, and roll up to obtain a coating layer;
[0075] S3: Compounding the composite layer, the coating layer, and the burr cloth composite material in sequence, heat setting, and compression molding to obtain a laminated composite coating foot pad;
[0076] The mass ratio of low-density polyethylene, polyethylene terephthalate, and chemically cross-linked polyethylene foam material in the composite layer is 2:1:1; the mass ratio of thermoplastic elastomer and chemically cross-linked polyethylene foam material in the coating layer is 1:3;
[0077] The working conditions of composite treatment are: screw speed of 45rpm, die temperature of 280℃, die width of 1500mm, and discharge roller gap of 0.03mm; the working conditions of coating treatment are: screw speed of 21.5Hz, roller speed of 6.65r / min; the working conditions of heat setting are: temperature of 160℃, time of 70s; the working conditions of compression molding are: time of 65s, pressure of 3MPa;
[0078] The preparation of the thermoplastic elastomer comprises the following steps: SEBS, PP and PE are mixed in a weight ratio of 20:45:35 to obtain a mixture; the mixture, a masterbatch, a stabilizer, calcium powder and an Optapol elastomer are mixed in a weight ratio of 87.6:0.3:0.1:2:10, extruded granulated, cooled, granulated and dried to obtain a thermoplastic elastomer;
[0079] The preparation of the chemically cross-linked polyethylene foam material comprises the following steps: mixing a low-density polyethylene resin, a cross-linking agent, an azo foaming agent, and a masterbatch according to a weight ratio of 96:0.7:0.3:2, extruding, and foaming to obtain a chemically cross-linked polyethylene foam material;
[0080] The preparation of polyethylene terephthalate comprises the following steps: mixing nylon particles and masterbatch in a weight ratio of 85:15, and melt spinning to obtain polyethylene terephthalate;
[0081] The burr cloth composite material is a modified burr cloth composite material, and the preparation thereof includes the following steps:
[0082] (3) preparing an antibacterial flame retardant impregnation liquid by mixing fluorinated silicone polyurethane and composite zinc phytate in a mass ratio of 20:1;
[0083] The preparation of the composite zinc phytate comprises the following steps:
[0084] 5.5 g of zinc acetate and 50 mL of deionized water were mixed, the temperature was raised to 82°C, a mixture of 6.6 g of phytic acid and 25 mL of deionized water was added, the mixture was kept warm for 4 h, washed and dried to obtain zinc phytate; 2 g of zinc phytate and 100 mL of ethanol were mixed, 2 g of 3,4-dihydroxybenzaldehyde and 1.6 g of quaternary ammonium glycogen were added, the mixture was kept warm at 82°C for 2 h, 3.2 g of DOPO was added, the mixture was stirred for 10 h, filtered, washed and dried to obtain composite zinc phytate;
[0085] The preparation of the fluorinated organosilicon polyurethane comprises the following steps:
[0086] 1) Under a nitrogen atmosphere, 5.3 g of isoborneol methacrylate, 2.4 g of dodecafluoroheptyl methacrylate, 0.3 g of 1-thioglycerol, 0.02 g of azobisisobutyronitrile and 24 mL of tetrahydrofuran were mixed, the temperature was raised to 72° C. and kept for 9 h, rotary evaporated, 20 mL of methanol was added and dried to obtain a hydroxylated fluorinated borneol copolymer;
[0087] 2) In a nitrogen environment, 10 mL of tetrahydrofuran, 2 g of hydroxyl-terminated polydimethylsiloxane, and 0.7 g of isophorone diisocyanate were mixed, the temperature was raised to 72° C. and kept warm for 1 h, 0.4 g of hydroxylated fluorinated borneol copolymer was added and kept warm for 40 min, 1 drop of dibutyltin dilaurate and 0.14 g of quaternary ammonium glycogen were added, the temperature was raised to 82° C. and kept warm for 2 h, 0.03 g of triethanolamine was added and kept warm for 2 h, and the material was discharged to obtain fluorinated silicone polyurethane;
[0088] The preparation of the quaternary ammonium salt glycogen comprises the following steps:
[0089] Under nitrogen protection, 4 g of glycogen and 200 mL of anhydrous dimethyl sulfoxide were mixed, 4 g of N, N-carbonyldiimidazole was added, and the mixture was stirred at 35°C for 1 h. A mixture of 6 mL of ethylenediamine and 10 mL of dimethyl sulfoxide was added, and the mixture was kept at 25°C for 22 h, dialyzed for 3 days, and freeze-dried to obtain amino glycogen; 2 g of amino glycogen and 25 mL of deionized water were mixed, stirred at 62°C for 20 min, the pH was adjusted to 9, 1 g of 2, 3-epoxypropyltrimethylammonium chloride was added, and the mixture was kept warm for 6 h, dialyzed for 3 days, and freeze-dried to obtain quaternary ammonium glycogen;
[0090] (2) The burr cloth composite material is immersed in an antibacterial and flame retardant impregnation liquid, and then dried to obtain a modified burr cloth composite material.
[0091] Comparative Example 1: Example 3 was used as a control group, in which no hydroxylated fluorinated borneol copolymer was prepared, and other processes were normal.
[0092] Comparative Example 2: Example 3 was used as the control group, quaternized glycogen was not prepared, and other processes were normal.
[0093] Comparative Example 3: Taking Example 3 as the control group, zinc phytate was used to replace the composite zinc phytate, and other processes were normal.
[0094] Source of raw materials (for demonstration only):
[0095] PE2426H (96%): Iran Persian Gulf Petrochemical Plant; Masterbatch 943: Shenzhen Hengcai Pigment Trading Co., Ltd.; Crosslinking agent DCP: Jiangsu Daoming Chemical Co., Ltd.; Azo foaming agent 1500E: Qingdao Xinnuo Chemical; Nylon granules: China Petrochemical Corporation; SEBSYH-506: Dongguan Yucheng Plastic Chemical Co., Ltd.; Low-density polyethylene resin LD 509.48: Dongguan Jinshixiang Plastic Raw Materials Co., Ltd.; PP9003-07-0: Hubei Qifei Pharmaceutical Chemical Co., Ltd.; Stabilizer 0270: Dongguan Suyu Chemical Co., Ltd.; Calcium powder (calcium oxide powder, AR): Fuchen (Tianjin) Chemical Reagent Co., Ltd.; Optapol elastomer 6365N: Anhui Jinke Opte Polymer Materials Co., Ltd.; Burr cloth composite material KBS006: Changshu Kaibos Needle Textile Co., Ltd.; Zinc acetate Z110777, phytic acid P350767, 3,4-dihydroxybenzaldehyde D108634, DOPO (9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide) D102416, Isoborneol methacrylate I102358, dodecafluoroheptyl methacrylate D301595, 1-thioglycerol T141418, azobisisobutyronitrile A434183, tetrahydrofuran T431413, isophorone diisocyanate I109582, hydroxyl-terminated polydimethylsiloxane P304442, dibutyltin dilaurate D100274, triethanolamine T108151, glycogen G111730, dimethyl sulfoxide D103272, N,N-carbonyldiimidazole C109315, ethylenediamine E112132, 2,3-epoxypropyltrimethylammonium chloride G298766: Aladdin reagent; ethanol, methanol, analytical grade: Sinopharm reagent.
[0096] Performance test: testing the modified burr cloth composite materials in the embodiments and comparative examples;
[0097] Antibacterial property: refer to GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method" Section 10.1.1 "Washing color fastness test machine washing method" for 15 standard washes to test the antibacterial property, and the strain used is Staphylococcus aureus ATCC6538; Flame retardancy: refer to UL-94 for vertical burning grade test; the test results are shown in Table 1;
[0098] Table 1
[0099] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Antibacterial rate (%) 99.9 99.9 100 92.1 91.9 88.3 Flame retardant grade V-0 V-0 V-0 V-1 V-1 V-1
[0100] The invention provides a laminated composite coated foot pad and a preparation method thereof, and a foot pad with good mechanical strength, excellent antibacterial property, good antifouling property and high flame retardancy is prepared by limiting raw materials and processes.
[0101] By comparing Example 3 with Comparative Examples 1 and 2, the organosilicon coating is an ideal environmentally friendly antifouling material, but its static antifouling ability is relatively poor. In the present invention, hydroxyl-terminated polydimethylsiloxane and isophorone diisocyanate are used as raw materials to synthesize an organosilicon prepolymer, and a hydroxylated fluorinated borneol copolymer prepared by free radical polymerization of isoborneol methacrylate, dodecafluoroheptyl methacrylate and 1-thioglycerol is used together with quaternized glycogen as a chain extender and triethanolamine as a capping agent to obtain a fluorinated organosilicon polyurethane. The quaternary ammonium glycogen is combined with the antifouling group to improve its static antifouling ability; the quaternary ammonium glycogen is a stepwise chemical modification on the glycogen, and the amino group is first modified to the glycogen side chain, which is conducive to its cross-linking with the fluorinated silicone polyurethane to enhance the antibacterial and flame retardant durability. Also, because the reaction activity of the amino group is stronger than that of the hydroxyl group, it is conducive to the subsequent quaternary ammonium salt modification, and the amino glycogen is quaternized to form a cationic dendritic macromolecular structure quaternary ammonium glycogen, while giving it excellent mechanical properties, good substrate adhesion, and excellent antibacterial properties.
[0102] Example 3 is compared with Comparative Example 3. Phytic acid is a biomass organophosphorus compound containing 6 phosphate groups and is an effective carbonizing agent, but its gas-phase flame retardant efficiency is low. In the present invention, phytic acid and zinc acetate are used to prepare zinc phytate, and then 3,4-dihydroxybenzaldehyde, quaternized glycogen and DOPO are used as raw materials to synthesize a Schiff base copolymer in one pot, and intermolecular forces are used to coat zinc phytate to prepare composite zinc phytate as a flame retardant and antibacterial agent, which is introduced into a flame-retardant and antibacterial impregnation solution, and the synergistic effect of DOPO-based flame retardants is used to compensate for the low gas-phase flame retardant efficiency of phytic acid, to form a heat-insulating carbon layer during combustion, and to shield air, heat and pyrolysis products during thermal decomposition; wherein the introduction of quaternized glycogen gives the composite zinc phytate excellent antibacterial properties.
[0103] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a laminated composite film-coated foot pad. It is characterized in that The following steps are involved: S1: low-density polyethylene is put into the hopper of the compounding machine, and polyethylene terephthalate and chemically cross-linked polyethylene foam material are respectively fed into rollers from both ends of the compounding machine, compounded, and rolled to obtain a composite layer; S2: Put the thermoplastic elastomer into the laminating machine hopper, clamp the chemically cross-linked polyethylene foam material between the rollers, perform coating treatment, and roll up to obtain a coating layer; S3: Compounding the composite layer, the coating layer, and the burr cloth composite material in sequence, heat setting, and compression molding to obtain a laminated composite coating foot pad; The burr cloth composite material is a modified burr cloth composite material, and the preparation thereof includes the following steps: (1) Preparation of antibacterial flame retardant impregnation liquid using fluorinated organosilicon polyurethane and composite zinc phytate; (2) placing the burr cloth composite material into an antibacterial flame retardant impregnation liquid for immersion treatment, and drying to obtain a modified burr cloth composite material; The preparation of the composite zinc phytate comprises the following steps: Mix zinc acetate and deionized water, heat to 78-82°C, add a mixture of phytic acid and deionized water, keep warm for 3-4 hours, wash and dry to obtain zinc phytate; mix zinc phytate and ethanol, add 3,4-dihydroxybenzaldehyde and quaternary ammonium glycogen, keep warm at 78-82°C for 2-3 hours, add DOPO, stir for 9-10 hours, filter, wash and dry to obtain composite zinc phytate; The preparation of the fluorinated organosilicon polyurethane comprises the following steps: 1) Under a nitrogen atmosphere, isoborneol methacrylate, dodecafluoroheptyl methacrylate, 1-thioglycerol, azobisisobutyronitrile and tetrahydrofuran are mixed, the temperature is raised to 68-72°C and kept for 9-10 hours, rotary evaporated, methanol is added, and dried to obtain a hydroxylated fluorinated borneol copolymer; 2) In a nitrogen environment, tetrahydrofuran, hydroxyl-terminated polydimethylsiloxane and isophorone diisocyanate are mixed, the temperature is raised to 68-72°C and kept for 1-2 hours, hydroxylated fluorinated borneol copolymer is added and kept for 30-40 minutes, dibutyltin dilaurate and quaternary ammonium glycogen are added, the temperature is raised to 78-82°C and kept for 2-3 hours, triethanolamine is added and kept for 1-2 hours, and the material is discharged to obtain fluorinated silicone polyurethane; The preparation of the quaternary ammonium salt glycogen comprises the following steps: Under nitrogen protection, glycogen and anhydrous dimethyl sulfoxide are mixed, N,N-carbonyldiimidazole is added, and the mixture is stirred at 30-35°C for 1-2 hours. A mixture of ethylenediamine and dimethyl sulfoxide is added, and the mixture is kept warm at 18-25°C for 22-24 hours, dialyzed, and freeze-dried to obtain amino glycogen; the amino glycogen and deionized water are mixed, and the mixture is stirred at 58-62°C for 20-30 minutes. The pH is adjusted to 8-9, 2,3-epoxypropyltrimethylammonium chloride is added, and the mixture is kept warm for 5-6 hours. The mixture is dialyzed and freeze-dried to obtain quaternary ammonium glycogen.
2. A method for preparing a laminated composite coated foot pad according to claim 1, It is characterized in that The mass ratio of low-density polyethylene, polyethylene terephthalate and chemically cross-linked polyethylene foam material in the composite layer is 2:1:1; the mass ratio of thermoplastic elastomer and chemically cross-linked polyethylene foam material in the coating layer is 1:
3.
3. A method for preparing a laminated composite coated foot pad according to claim 1, It is characterized in that The preparation of the thermoplastic elastomer comprises the following steps: SEBS, PP and PE are mixed in a weight ratio of 20:45:35 to obtain a mixture; the mixture, masterbatch, stabilizer, calcium powder and Optapol elastomer are mixed in a weight ratio of 87.6:0.3:0.1:2:10, extruded into granules, cooled, pelletized and dried to obtain a thermoplastic elastomer.
4. A method for preparing a laminated composite coated foot pad according to claim 1, It is characterized in that The preparation of the chemically cross-linked polyethylene foam material comprises the following steps: mixing a low-density polyethylene resin, a cross-linking agent, an azo foaming agent and a masterbatch according to a weight ratio of 96:0.7:0.3:2, extruding, and foaming to obtain the chemically cross-linked polyethylene foam material.
5. A laminated composite film foot pad, It is characterized in that The compound is prepared by the preparation method according to any one of claims 1 to 4.
Citation Information
Cited By
Antibacterial mildew-proof plastic foot pad and preparation method thereof
CN121084017A
